Effect of beetroot juice supplementation on swimming performance - Roberto, S.; Pinna, M.; Milia, R.; Marongiu, E.; Olla, S.; Loi, A.; Migliaccio, G. M.; Tocco, F.; Concu, A.; Crisafulli, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Recent evidence suggests that beetroot juice supplementation (BJS) may improve the physiological responses to exercise (Bailey et al. 2009). The beneficial effects of BJS have been tested during cycling, walking, and running. However, to the best of our knowledge none has investigated on its effect during swimming, probably because the measurement of certain physiological parameters such as oxygen uptake (VO2) and anaerobic threshold (AT) during swimming suffers from technical limitations. The aim of the present study was to discover whether BJS could improve performance in swimmers. Methods: Fourteen moderately trained male master swimmers were recruited and underwent two incremental swimming test in a pool: a control swimming test (CSW), and the other was a swimming test after six days of dietary supplementation with NO3- rich beetroot juice (0.5l/day organic beetroot juice containing about 5.5 mmol of NO3- ). During each test workload, oxygen uptake (VO2), carbon dioxide production (VCO2), pulmonary ventilation (VE), and aerobic energy cost (AEC) of swimming were measured by means of a portable gas analyser (VO2000, MedicGraphics, USA) through telemetric transmission. This system has been shown previously used during swimming (Pinna et al. 2013). Results: Results show that workload at anaerobic threshold was significantly increased by BJS as compared to the CSW test (6.3 ± 1 and 6.7 ± 1.1 kg during the CSW and the BJS test respectively). Moreover, BJS reduced aerobic energy cost of swimming at submaximal workload, as shown by the significantly reduced of AEC at anaerobic threshold during the BJS test (1.9 ± 0.5 during the SW test vs. 1.7 ± 0.3 kcal/kg/h during the BJS test). This finding is in agreement with previous research showing that dietary NO3- supplementation by beetroot juice can reduce aerobic cost of submaximal strain in various kinds of exercise (Bailey et al. 2009). None of the other variables were affected by BJS. Discussion: The present investigation provides evidence that BJS can positively affect performance of swimmers as it reduces the AEC and increases the workload at anaerobic threshold. Further research is needed to clarify whether beetroot juice supplementation may be beneficial also for highly trained swimmers.